Respuesta :
Hello!
[tex]S=-55/13[/tex]
Simplify both sides of the equation
[tex]2-2s=3/5s+13[/tex]
[tex]2+-2s=3/5s+13[/tex]
[tex]-2s+2=3/5s+13[/tex]
Subtract 3/5s from both sides
[tex]-2s+2-3/5s=3/5s+13-3/5s[/tex]
[tex]-13/5s+2=13[/tex]
Subtract 2 from both sides
[tex]-13/5s+2-2=13-2[/tex]
[tex]-13/5s=11[/tex]
Multiply both sides by 5/(-13)
[tex](5/-13)*(-13/5s)=(5/-13)*11[/tex]
Answer:
s=-55/13
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2−2s=35s+13
2+−2s=35s+13
−2s+2=35s+13
Step 2: Subtract 3/5s from both sides.
−2s+2−35s=35s+13−35s
−135s+2=13
Step 3: Subtract 2 from both sides.
−135s+2−2=13−2
−135s=11
Step 4: Multiply both sides by 5/(-13).
(5−13)*(−135s)=(5−13)*(11)
s=−55/13